Habitat Selection and Population Density of Diurnal and Nocturnal Lemurs in the Anjozorobe-Angavo Protected Area, Madagascar - Giulia Sassoli; Aurelia Sebastiani; Davide Mirante; Hanitriniaina Raharinirina; Rojotiana N. Rakotoarisoa; N. M. Koloina Rakotoarivelo; Fanomezantsoa L. Ravololoniaina; H. Domohina S. Randrianarisoa; Gabriele Ferraro; S. Jacques Rakotondranary; Timothy M. Eppley; Luca Santini (International Journal of Primatology, 2026)
Primates are among the most threatened mammals globally owing to rapid habitat loss and intense hunting pressure. Among these, lemurs are the taxon with the highest number of species at risk of extinction. Although many lemur species have been surveyed extensively across Madagascar, some taxa and protected areas remain understudied. The Anjozorobe-Angavo Protected Area, a rainforest landscape in the highlands of central-eastern Madagascar, has received relatively little ecological attention and continues to experience deforestation. This study was designed to estimate the population density and habitat selection of diurnal and nocturnal lemur species within La Mananara, a privately owned forest within Anjozorobe-Angavo. We conducted line-transect surveys over a 3-month period, between October and December 2024, and applied distance sampling to estimate species abundance. We also collected data on species detection locations and established vegetation plots to characterize habitat structure and evaluate species-specific habitat associations through resource selection functions. We recorded four diurnal and six nocturnal lemur species. Nocturnal species exhibited higher estimated densities and were more frequently encountered in areas with human activity, whereas diurnal species were less abundant and generally showed stronger associations with areas characterized by greater canopy cover and lower anthropogenic disturbance. Our findings underscore the conservation importance of primary forest protection, while also demonstrating the role of edge habitat and human-modified habitats for certain nocturnal taxa. These density estimates represent a quantitative assessment for this area, helping to inform the management of La Mananara, and contributing to broader conservation assessments of lemur populations within this under-characterized protected landscape.

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

Seismically triggered anoxia and brine spillover during the CE 365 Crete mega-earthquake in the eastern Mediterranean Sea - A. Polonia; A. Asioli; L. Ferraro; E. Colizza; F. Corticelli; G.J. de Lange; A. Gallerani; G. Gasparotto; L. Gasperini; G. Giorgetti; V. La Cono; G. La Spada; et al. (Gondwana Research, 2026)

Detection of Dengue virus RNA in Wastewater during a Local Epidemic in Central Italy (August–October 2024) - P. Mancini; C. Veneri; G. Bonanno Ferraro; A. Franco; M. Iaconelli; D. Brandtner; L. Lucentini; G. Venturi; E. Mancuso; G. Marsili; M. Del Manso; C. Sacco; et al. (Food and Environmental Virology, 2025)

The use and abuse of ecosystem service concepts and terms - Kristy M. Ferraro; Anthony L. Ferraro; Erick Lundgren; Nathalie R. Sommer (Biological Conservation, 2025)

Sedimentological and biostratigraphic reconstruction of the Early Pleistocene San Giuliano Lake section (Matera, Southern Italy) - F.O. Amore; C. Argenio; C. Faranda; L. Ferraro; E. Gliozzi; D. Magri; F. Michelangeli; B. Russo; J. Siciliano; M. Vallefuoco; A. Mauro; A. Meo; et al. (Quaternary International, 2025)

Climate change and occupational health and safety. Risk of injuries, productivity loss and the co-benefits perspective - A. Marinaccio; C. Gariazzo; L. Taiano; M. Bonafede; D. Martini; S. D'Amario; F. de’Donato; M. Morabito; Filippo Ariani; Alessandra Binazzi; Andrea Bogi; Michela Bonafede; et al. (Environmental Research, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Global quantification and distribution of antibiotic resistance genes in oceans and seas: Anthropogenic impacts and regional variability - G. Bonanno Ferraro; D. Brandtner; A. Franco; M. Iaconelli; P. Mancini; C. Veneri; R. Briancesco; A.M. Coccia; E. Suffredini; A. Muratore; F. Ferrara; L. Lucentini; et al. (Science of The Total Environment, 2024)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

Exploring the underwater life in transitional environments: Benthic foraminifera, ostracods, and dinoflagellate cysts – Biotic trends and EcoQS assessment in the Mar Piccolo of Taranto (Ionian sea, southern Italy) - F. Francescangeli; L. Ferraro; F. Frontalini; S. Da Prato; F. Rubino (Marine Environmental Research, 2024)

Tracing the footprints of SARS-CoV-2 in oceanic waters - Giuseppina La Rosa; P. Mancini; M. Iaconelli; C. Veneri; G. Bonanno Ferraro; C. Del Giudice; E. Suffredini; A. Muratore; F. Ferrara; L. Lucentini; M. Martuzzi; A. Piccioli (Science of The Total Environment, 2024)

Revisiting two dogmas of conservation science - Kristy M. Ferraro; Anthony L. Ferraro; A. Z. Andis Arietta; Nathalie R. Sommer (Conservation Biology, 2023)
Conservation science is a morally motivated field, with implicit and explicit values built into its practice. As such, conservationists must engage with conservation ethics to interrogate underlying values. We examine cutting‐edge ecological science and contemporary ethics to revisit two conservation norms that have become dogmatic in the field: ecological collectives, but not individual animals, are valuable and anthropomorphism should be staunchly avoided. Emerging studies demonstrate that individuals and their intraspecific variation can be instrumentally valuable for conservation science, and there is an emerging consensus within environmental philosophy around the moral worth of individuals. Thus, we suggest conservation science should explicitly recognize the value of individuals. We also argue that avoiding anthropomorphism is detrimental to conservation because critical anthropomorphism enables a more nuanced scientific approach—allowing conservationists to ask enlightened questions with creativity and compassion. We provide evidence that both dogmatic norms are scientifically and morally outdated and propose new normative values to push conservation towards more robust science and ethical practice.

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

A State-of-the-Art Scoping Review on SARS-CoV-2 in Sewage Focusing on the Potential of Wastewater Surveillance for the Monitoring of the COVID-19 Pandemic - G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; E. Suffredini; L. Bonadonna; L. Lucentini; A. Bowo-Ngandji; C. Kengne-Nde; D. S. Mbaga; G. Mahamat; H. R. Tazokong; et al. (Food and Environmental Virology, 2022)

Hepatitis E Virus in Water Environments: A Systematic Review and Meta-analysis - G. R. Takuissu; S. Kenmoe; L. Ndip; J. T. Ebogo-Belobo; C. Kengne-Ndé; D. S. Mbaga; A. Bowo-Ngandji; M. G. Oyono; R. Kenfack-Momo; S. Tchatchouang; J. Kenfack-Zanguim; R. Lontuo Fogang; et al. (Food and Environmental Virology, 2022)
Hepatitis E virus (HEV) is responsible for acute hepatitis in humans, through foodborne, zoonotic, and waterborne transmission routes. This study aimed to assess the prevalence of HEV in water matrices. Six categories were defined: untreated and treated wastewater, surface water (river, lake, and seawater), drinking water, groundwater, and other water environments (irrigation water, grey water, reservoir water, flood water, and effluent of pig slaughterhouse). We searched PubMed, Web of Science, Global Index Medicus, and Excerpta Medica Database. Study selection and data extraction were performed by at least two independent investigators. Heterogeneity ( I 2 ) was assessed using the χ 2 test on the Cochran Q statistic and H parameter. Sources of heterogeneity were explored by subgroup analysis. This study is registered with PROSPERO, number CRD42021289116. We included 87 prevalence studies from 58 papers, 66.4% of which performed in Europe. The overall prevalence of HEV in water was 9.8% (95% CI 6.4–13.7). The prevalence was higher in untreated wastewater (15.1%) and lower in treated wastewater (3.8%) and in drinking water (4.7%). In surface water, prevalence was 7.4%, and in groundwater, the percentage of positive samples, from only one study available, was 8.3%. Overall, only 36.8% of the studies reported the genotype of HEV, with genotype 3 (HEV-3) prevalent (168 samples), followed by HEV-1 (148 sample), and HEV-4 (2 samples). High-income countries were the most represented with 59/87 studies (67.8%), while only 3/87 (3.5%) of the studies were performed in low-income countries. The overall prevalence obtained of this study was generally higher in industrialized countries. Risk of bias was low in 14.9% of the studies and moderate in 85.1%. The results of this review showed the occurrence of HEV in different waters environments also in industrialized countries with sanitation and safe water supplies. While HEV transmission to humans through water has been widely demonstrated in developing countries, it is an issue still pending in industrialized countries. Better knowledge on the source of pollution, occurrence, survival in water, and removal by water treatment is needed to unravel this transmission path. Graphical Abstract

Pepper Mild Mottle Virus as Indicator of Pollution: Assessment of Prevalence and Concentration in Different Water Environments in Italy - G. Bonanno Ferraro; E. Suffredini; P. Mancini; C. Veneri; M. Iaconelli; L. Bonadonna; M. T. Montagna; O. De Giglio; G. La Rosa (Food and Environmental Virology, 2021)

In situ and ex situ bioremediation of seleniferous soils from northwestern India - Shrutika L. Wadgaonkar; Alberto Ferraro; Yarlagadda V. Nancharaiah; Karaj S. Dhillon; Massimiliano Fabbricino; Giovanni Esposito; Piet N. L. Lens (Journal of Soils and Sediments, 2019)

Historical maps and satellite images as tools for shoreline variations and territorial changes assessment: the case study of Volturno Coastal Plain (Southern Italy) - I. Alberico; G. Cavuoto; V. Di Fiore; M. Punzo; D. Tarallo; N. Pelosi; L. Ferraro; E. Marsella (Journal of Coastal Conservation, 2018)

Winter precipitation characteristics in western US related to atmospheric river landfalls: observations and model evaluations - J. Kim; B. Guan; D. E. Waliser; R. D. Ferraro; J. L. Case; T. Iguchi; E. Kemp; W. Putman; W. Wang; D. Wu; B. Tian (Climate Dynamics, 2018)

A multidisciplinary approach to study confined marine basins: the holobenthic and merobenthic assemblages in the Mar Piccolo of Taranto (Ionian Sea, Mediterranean) - L. Ferraro; F. Rubino; M. Belmonte; S. Da Prato; M. Greco; F. Frontalini (Marine Biodiversity, 2017)

Cytoskeletal Alterations and Biomechanical Properties of parkin-Mutant Human Primary Fibroblasts - Daniele Vergara; Marzia M. Ferraro; Mariafrancesca Cascione; Loretta L. del Mercato; Stefano Leporatti; Anna Ferretta; Paola Tanzarella; Consiglia Pacelli; Angelo Santino; Michele Maffia; Tiziana Cocco; Ross Rinaldi; et al. (Cell Biochemistry and Biophysics, 2015)

Multi-center evaluation of the VITEK® MS system for mass spectrometric identification of non-Enterobacteriaceae Gram-negative bacilli - R. Manji; M. Bythrow; J. A. Branda; C.-A. D. Burnham; M. J. Ferraro; O. B. Garner; R. Jennemann; M. A. Lewinski; A. B. Mochon; G. W. Procop; S. S. Richter; J. A. Rychert; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

Identification of Enterobacteriaceae by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry using the VITEK MS system - S. S. Richter; L. Sercia; J. A. Branda; C.-A. D. Burnham; M. Bythrow; M. J. Ferraro; O. B. Garner; C. C. Ginocchio; R. Jennemann; M. A. Lewinski; R. Manji; A. B. Mochon; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Current views on EDDS use for ex situ washing of potentially toxic metal contaminated soils - M. Fabbricino; A. Ferraro; G. Del Giudice; L. d’Antonio (Reviews in Environmental Science and Bio/Technology, 2013)

Recorded ground motion and site effects evaluation for the April 6, 2009 L’Aquila earthquake - M. Maugeri; A. L. Simonelli; A. Ferraro; S. Grasso; A. Penna (Bulletin of Earthquake Engineering, 2011)

New evidences of Roundup® (glyphosate formulation) impact on the periphyton community and the water quality of freshwater ecosystems - María S. Vera; Leonardo Lagomarsino; Matías Sylvester; Gonzalo L. Pérez; Patricia Rodríguez; Hernán Mugni; Rodrigo Sinistro; Marcela Ferraro; Carlos Bonetto; Horacio Zagarese; Haydée Pizarro (Ecotoxicology, 2010)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

A Factor Influence Study of Trace Element Bioaccumulation in Moss Bags - M. Cesa; B. Campisi; A. Bizzotto; C. Ferraro; F. Fumagalli; P. L. Nimis (Archives of Environmental Contamination and Toxicology, 2008)

Burkholderia cepacia complex nasal isolation in immunocompetent patients with sinonasal polyposis not associated with cystic fibrosis - G. Marioni; R. Rinaldi; C. Staffieri; G. Ottaviano; R. Marchese-Ragona; L. Giacomelli; S. M. Ferraro; A. Staffieri (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Fine mapping of a seizure susceptibility locus on mouse Chromosome 1: nomination of Kcnj10 as a causative gene - Russell J. Buono; Thomas N. Ferraro; Gregory T. Golden; George G. Smith; James F. Martin; Falk W. Lohoff; Tracy A. Gieringer; Deborah Zamboni; Candice L. Schwebel; Danielle M. Press; Stephanie Hongyu O. KratzerZhao; Wade H. Berrettini (Mammalian Genome, 2004)

Phototoxic Evaluation of Marine Sediments Collected from a PAH-Contaminated Site - B. L. Boese; R. J. Ozretich; J. O. Lamberson; F. A. Cole; R. C. Swartz; S. P. Ferraro (Archives of Environmental Contamination and Toxicology, 2000)

Verification of a scattering-based algorithm for estimating rainfall over the open ocean - J. S. Greene; M. L. Morrissey; R. R. Ferraro (Theoretical and Applied Climatology, 1997)